2022
DOI: 10.1002/etc.5519
|View full text |Cite
|
Sign up to set email alerts
|

Physical–Chemical Recovery of a Montane Stream After Remediation of Acid Mine Drainage: Timing and Extent After Turning off the Tap

Abstract: We monitored physical-chemical conditions in the North Fork of Clear Creek in Colorado (USA) before, during, and after the start of remediation (lime treatment) to remove metals from two major inputs of acid mine drainage (AMD) water. In addition, we analyzed historical monitoring data that extended back more than two decades. Concentration-discharge (C-D) and load-discharge (L-D) plots accounted for discharge dependence in concentrations and loads of metals, major ions, and other water chemistry parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Spatial and temporal variation in concentrations of major ions and conductivity at BTP, Gage, and Main suggest that these patterns were associated with the water treatment facility. In contrast to patterns observed at station BNT after mining‐related effluents were diverted, conductivity and concentrations of major ions downstream of the treatment facility either changed little or increased after remediation (Meyer et al, 2022 ). We hypothesize that in addition to metals, elevated concentrations of major ions impeded full recovery.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Spatial and temporal variation in concentrations of major ions and conductivity at BTP, Gage, and Main suggest that these patterns were associated with the water treatment facility. In contrast to patterns observed at station BNT after mining‐related effluents were diverted, conductivity and concentrations of major ions downstream of the treatment facility either changed little or increased after remediation (Meyer et al, 2022 ). We hypothesize that in addition to metals, elevated concentrations of major ions impeded full recovery.…”
Section: Discussionmentioning
confidence: 98%
“…The inverse relationship between Cu and Fe is toxicologically important, because 1) mesocosm experiments have shown that Cu and Fe are responsible for much of the toxicity to benthic organisms relative to their aquatic life criterion values (Clements et al, 2019 ), and 2) their concentrations in surface waters are regulated in the United States and most other jurisdictions around the world. In the NFCC, the percentage of Cu that is dissolved is strongly and inversely correlated with the particulate Fe concentration (Meyer et al, 2022 ). This relationship in part explains why the concentration of dissolved Cu at Gage decreased by only 20% after treatment whereas the total Cu concentration decreased by 67% (Meyer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations